A user guide to Malawi Africa research in sustainable intensification for the next generation (Africa RISING) baseline evaluation survey data - Azzarri, Carlo; Haile, Beliyou; Roberts, Cleophelia; Comanescu, Maria; Schnitzer, Pascale; Invest in Knowledge Initiative; Shee, Apurba (International Food Policy Research Institute, 2016)
The Malawi Africa Research in Sustainable Intensification for the Next Generation (Africa RISING) Baseline Evaluation Survey (MARBES) survey was implemented during July–October 2013 as part of IFPRI’s Monitoring and Evaluation (M&E) of Africa RISING. The Africa RISING program aims to create—through action research and development partnerships—opportunities for smallholder farmers in Africa south of the Sahara to sustainably intensify their farming systems and to improve their food, nutrition, and income security. Initiated in 2012, the program is supported by the United States Agency for International Development (USAID) as part of the U.S. government’s Feed the Future (FTF) initiative. As part of the program, the International Institute of Tropical Agriculture (IITA) leads a sustainable intensification effort focusing on the cereal-based farming systems in the Guinea Savannah Zone of West Africa (Ghana and Mali) and East and Southern Africa (Malawi, Tanzania, and Zambia), while the International Livestock Research Institute (ILRI) leads the research activities focusing on the crop-livestock systems of the Ethiopian highlands. The International Food Policy Research Institute (IFPRI) has been tasked with M&E of the three projects. Malawi Africa RISING is being implemented in Dedza and Ntcheu districts of the Central Region of Malawi, within the FTF Zones of Influence. The research activities are led by Michigan State University (MSU). MARBES collected detailed household- and plot-crop level data addressing various topics: employment (agricultural and non-agricultural); health; agricultural land; crop inputs, harvest, storage, and sale; livestock ownership, feed, and water; agriculture-related challenges and coping strategies; credit and off-farm income sources; housing conditions and ownership of various durable assets; subjective welfare and food security; household-level food consumption; non-food expenditure; agricultural shocks; and child and women anthropometry. The village survey collected data on access to basic services; access to extension services; social organizations, mobility, and village-level shocks; access to natural resources; metric conversion units; and prices of crops and food items. MARBES covered 1,149 households and 54 villages drawn from the two project districts. Data was collected using structured questionnaires in the local language (Chichewa), through Computer Assisted Personal Interviewing (using SurveyCTO).